Analysis of Short-term Outcomes of Totally Extraperitoneal and Extended Totally Extraperitoneal Repair of Ventral Hernia - Thorat, Santosh D; Bilaskar, Rajeev P (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Ventral hernias of the abdomen are defined as a non-inguinal, non-hiatal defect in the fascia of the abdominal wall. Annually, there are about 350,000 ventral hernia operations. Its repair is one of the most common surgical procedures performed by surgeons worldwide. Since the beginning of surgical history, treatment of hernia has evolved through different stages. The technique of e-TEP can also be applied for ventral hernia repair in 2017. The retro muscular e-TEP/e-RS approach combines the advantages of the sublay position of the mesh along with the benefits of the minimal invasiveness of the procedure. A prospective observational study was conducted among 60 patients with non-complicated ventral hernia who were randomized into two equal groups, equally, who were further subjected to either TEP or e-TEP laparoscopic ventral hernia repair. Patients posted for surgery received similar perioperative management. In the entire study, the p-values less than 0.05 are statistically significant. The data was analyzed using the Statistical Package for Social Sciences. Distribution of median duration of surgery among the cases studied was significantly higher in the Laparoscopic e-TEP repair group as compared to the Laparoscopic TEP repair group. e-TEP has an advantage over TEP owing to the less steep learning curve, with a wider angle view, a greater degree of movements for instruments, and ergonomically better operative experience. In conclusion, laparoscopic e-TEP hernia repair is the better modality of treatment for uncomplicated reducible ventral hernias in terms of wider working space, lower conversion rates, and lenient learning curve.